PENGARUH FINANCIAL LITERACY, PARENT INCOME, HEDONISME TERHADAP MANAJEMEN KEUANGAN MAHASISWA PADA MASA PANDEMI COVID-19 - Mahmudah, Nurul; Retnosari, Retnosari (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2021)
The COVID-19 pandemic triggered significant changes to the economic sector which affects the personal economy. This impact affects the behavior of financial management. One of the groups that affected are students who run into a shift in needs. The study aims to examine the effect of financial literacy, parent income, and hedonism on student financial management during the COVID-19 pandemic. The dependent variable in this study is financial management behavior, while the independent variables are financial literacy, parent income, and hedonism. The population and sample in this study were students of the S1 Accounting study program, Faculty of Economics, Tidar University class 2018. The research methodology used in this study was a quantitative approach, and data analysis used multiple linear regression through the SPSS program. The results showed that the financial literacy and hedonism variables had a positive and significant effect on student financial management behavior during the COVID-19 pandemic, while the variable that had no effect on student financial management behavior during the COVID-19 pandemic was parent income.